2008
DOI: 10.1111/j.1365-2710.2008.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Recommended dose of arbekacin, an aminoglycoside against methicillin-resistantStaphylococcus aureus, does not achieve desired serum concentration in critically ill patients with lowered creatinine clearance

Abstract: In critically ill patients with lowered CCR, the ABK dose for normal CCR subjects does not elevate its serum concentration to effective levels because of augmented V(d) caused by increased k(12). The present results hypothesize that adjustment of antibiotic dosing according to CCR further lowers C(max) in critically ill patients with reduced CCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…We showed that, because of PK alterations, a loading dose of ≥ 25 mg/kg of amikacin is necessary to achieve therapeutic peak concentrations in patients with severe sepsis or septic shock. Antimicrobials PKs in ICU patients are significantly different from those in healthy volunteers or less severely ill patients [14,31,32]. Increased cardiac index and interstitial fluid shifts in sepsis result in a larger volume of distribution (V d ), which may reduce plasma antibiotic levels [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that, because of PK alterations, a loading dose of ≥ 25 mg/kg of amikacin is necessary to achieve therapeutic peak concentrations in patients with severe sepsis or septic shock. Antimicrobials PKs in ICU patients are significantly different from those in healthy volunteers or less severely ill patients [14,31,32]. Increased cardiac index and interstitial fluid shifts in sepsis result in a larger volume of distribution (V d ), which may reduce plasma antibiotic levels [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although aminoglycoside pharmacokinetics (PKs) have been already described for the treatment of ICU infections, studies on optimal regimens in sepsis patients had several limiting factors [14-18]. Few prospective data are available regarding which aminoglycoside dose should be used to optimize aminoglycoside concentrations in ICU patients with severe sepsis and septic shock with multiple organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Karakteristik farmakokinetik antibiotik pada pasien yang dirawat di PICU berbeda signifikan dibandingkan dengan pasien dengan orang sehat atau pasien dengan mild disease/non critically ill (Fukuoka and Aibiki, 2008). Pada pasien critically ill, sangat penting dalam memperhatikan faktor-faktor yang mempengaruhi perubahan patofisiologis dalam parameter farmakokinetik dan farmakodinamik dari antibiotik yang diberikan (Pichala dkk., 2013) pasien anak dengan penyakit penyerta/ komorbid (13,9%) jika dibandingkan dengan mereka yang tidak memiliki penyakit penyerta (6,4%) (El Halal dkk., 2012).…”
Section: Hasil Dan Pembahasanunclassified